Antibody response to Newcastle disease virus recombinant fusion protein in post-vaccinated laying hens - J. Jawad; R. W. Astuti; A. Haryanto; N. Wijayanti (Diponegoro University, 2023)
This research was aimed to analyze antibody response in laying hens post vaccinated by Newcastle Disease Virus (NDV) recombinat Fusion (F) protein which has been succesfully expressed from the F gene of local isolates of NDV from Kulon Progo strain (0663/04/2013), Yogyakarta, Indonesia. The F gene cloned into expression vector plasmid pBT7-N-His. Two types of NDV recombinant vaccine, a concentrated and pure F recombinant protein were used for vaccination. A concentrated recombinant F protein was collected from the centrifugal ultrafiltration process and a pure recombinant F protein was collected from the electroeluted process. Recombinant F protein of NDV was successfully expressed, purified, and visualized by Sodium Dodecyl Sulphate–Polyacrylamide Gel Electrophoresis (SDS-PAGE) with Coomassie Brilliant Blue staining with a molecular weight of 28 kDa. All two types of recombinant F vaccines and a commercial live vaccine as a positive control were injected two times at 14 and 18th weeks old laying hens to analyze the antibody response in serum. In comparison with a commercial live NDV vaccine, indirect Enzyme-linked Immunosorbent Assay (ELISA) revealed that antibody responses were high in both recombinant F protein vaccinated groups. In conclusion, the recombinant F protein has the potential to be developed as a recombinant vaccine candidate to obtain a higher antibody response in laying hens compared to commercially available live NDV vaccines.